"Campanha de formação do paraíso por meio das flores": a influência da arte Ikebana Sanguetsu na espiritualidade de membros e frequentadores da Igreja Messiânica Mundial do Brasil - Leite, Tadeu Ulisses Barros (2016)
This research aims to reflect on the connection between religion and art on the philosophical and practical basis of the World Messianic Church of Brazil (IMMB), according to Mokichi Okada, and to analyze the influence of the Ikebana Sanguetsu Art on the spirituality of members and non-members of this institution. It was used on this research the bibliographical review methodology and the application of two questionnaires of interview with the subjects: (1) Underwood`s Spiritual Everyday life Modified Experience Scale and (2) Questionnaire about the practice and appreciation of the Ikebana Sanguetsu Art. The questionnaires were applied to 76 people, 57 members and 19 non-members of the institution, randomly raffled from the IMMB register, including São Paulo state region. First it was asked to the participants to read and sign an authorization (Termo de Consentimento Livre e Esclarecido). The participants who declared not to know the Ikebana Sanguetsu Art were excluded from the study. The data was analyzed in two phases: the first was quantitative and it was used the Statistical Package for Social Sciences – SPSS; the second was qualitative